A new ETFE façade creates a landmark for Puebla F.C. Issue 2 (May 2016) - Aracil Llinares, Mónica; Schöne, Lutz; Weininger, Florian
Abstract: Cuauhtémoc Stadium, a first division football stadium in Puebla, México, with more than 51 000 seats, has recently been completely renovated. The brand‐new façade has become an icon for the club and for the city. The façade is designed as a skin of single‐layer ETFE foil in a combination of three different shades of blue and translucent white. The design and construction of the façade is the result of an international collaboration between local contractor DÜNN Lightweight Architecture, from Zapopan, Mexico, and LEICHT Structural engineering and specialists consulting GmbH, based in Munich, Germany. This paper will elaborate on the boundary conditions of the project and the technical decisions made for the construction of the façade.